Malware Analysis Using Apis Pattern Mining - Turki Obeis, Nawfal; Bhaya, Wesam (International Journal of Engineering and Technology, 2018)
Malicious code threats cybersecurity. Malware and its detection have caught the challenges of both anti-malware industry and researchers for decades.We use pattern mining technique to find the frequent Windows Application Program Interface (API) calls and then uses the frequent item sets to build the sequence of features for next analysis. Shingling techniques have proven effective for the problem of detecting. For verification, we use clustering processes of malware sequences based on their frequent API call sequences.We have achieved a high detection rate of 99.029% with accuracy as high as 98.8%. Thus, proposal method improved state of the art technology in several aspects: accuracy, detection rate, and false alarm rate were decreased.The experiment upon a big API sequence dataset demonstrated that the using frequent of API call sequences could realize a high accuracy for malware clustering while dropping the computation time.Â Â Â